Estimating the cost of Irish housing for the CPI: A rental equivalence approach - Matthew Allen-Coghlan; Cathal Coffey; Maria Martinez-Cillero; Ilias Kostarakos; Kieran McQuinn; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2020)
In this paper, we implement a new measure, the rental equivalence approach, in estimating the cost of Irish housing for the purposes of the consumer price index (CPI). The cost of housing composes both the cost of owner occupier housing (OOH) as well as the cost of renting. This work, which is in conjunction with the Central Statistics Office (CSO), follows earlier work, which reviewed the different, existing approaches taken by the CSO in estimating the cost of housing. The rental equivalence approach - used to calculate the cost of OOH - seeks to isolate the consumption element of owning a home, which is consistent with its usage in the CPI. The proposed approach also benefits from the usage of existing rental indices, which are compiled and estimated by researchers in the Economic and Social Research Institute (ESRI) for the Rental Tenancy Board (RTB).
Keywords: E31; R20; P44; 330; Housing; Inflation; Rental Equivalence; CPI